Usability Insight of Animated Infographic Module in Arabic Grammar Learning - Hamid, Mohd Fauzi Abdul; Halim, Zulazhan Ab.; Sahrir, Muhammad Sabri; Yahaya, Mohd Firdaus (The journal of contemporary issues in business and government, 2021)
The use of multimedia technology in teaching and learning in Arabic grammar is very crucial in line with the needs and interests of today's students. As such, an animated infographic module in learning Arabic grammar has been developed to adapt the use of this instructional mean. This study aimed to evaluate the usability of an infographic module known as the iGQA Module. The process of module development employed a Design and Development (DDR) approach which involved few phases such as needs analysis, design and development phase, and usability evaluation phase. This study adapted a survey method to evaluate the developed modules. Questionnaire instruments were distributed to 74 students of ISM Arabic Studies, Sultan Zainal Abidin University who participated in the online module learning sessions. Data were analysed descriptively using the Statistical Package for Social Science (SPSS). The results showed that the level of student satisfaction is high on the elements applied in the module. In conclusion, the developed modules help students to understand Arabic grammar easily and are able to pique their interest in learning it.